2004
DOI: 10.1126/science.1099944
|View full text |Cite
|
Sign up to set email alerts
|

A Compound from Smoke That Promotes Seed Germination

Abstract: Exposure of seeds to aerosol smoke or crude smoke extracts stimulates the germination of a number of fire-dependent and fire-independent plant species. We now report the identity of a germination-promoting compound present in plant- and cellulose-derived smoke. The structure of this compound, deduced from spectroscopic analysis and confirmed by synthesis, was shown to be that of the butenolide 3-methyl-2H-furo[2,3-c]pyran-2-one (1). Here we show that 1 promotes germination of a number of plant species at a lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
481
0
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 635 publications
(499 citation statements)
references
References 4 publications
6
481
0
12
Order By: Relevance
“…Our investigation into the A. manglesii germination stimulant revealed that it was not produced by the burning of cellulose, a substrate that is known to produce karrikinolide 11 . Instead, combustion of plant material was required to obtain smoke-water extracts that stimulated the germination of A. manglesii (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our investigation into the A. manglesii germination stimulant revealed that it was not produced by the burning of cellulose, a substrate that is known to produce karrikinolide 11 . Instead, combustion of plant material was required to obtain smoke-water extracts that stimulated the germination of A. manglesii (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Testing of an authentic racemic sample of glyceronitrile 20 against seeds of A. manglesii and the South African species Rhodocoma arida (Restionaceae), which also responds poorly to karrikinolide 11 , confirmed that glyceronitrile (2) was bioactive with both species (Fig. 3a,b).…”
Section: Confirmation Of Germination Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…Periods of (moist) cold stratification (4-5 C) for up to 90 d can increase germination percentage and rate in the woody species Allocasuarina verticillata (Moncur et al, 1997), Eucalyptus pauciflora (Beardsell and Mullett, 1984) and in one provenance of Banksia saxicola (Middleton et al, 1996), but no studies have tested the effect of warm stratification on seed dormancy-break in Australian species. Other studies have found that seeds of many Australian species are responsive to smoke and smoke products (Dixon et al, 1995;Flematti et al, 2004;Merritt et al, 2006), thermic pulsing (Tieu et al, 2001a), afterripening (Schutz et al, 2002) and light . Nevertheless, there remain a number of common Australian species that do not respond to these treatments and are difficult to germinate (Dixon et al, 1995;Tieu et al, 2001b;Merritt and Dixon, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical identity of the germination cue has recently been characterized as 3-methyl-2H-furo[2,3-c]-pyran-2-one ( Figure 1) from burned cellulose (11) and plantderived smoke (12). It can promote seed germination at concentrations as low as 10 -9 M (11,12), although the mode of action of this compound in promoting germination it still unknown and will require further research. In some earlier studies on smoke-stimulated germination, the effect of different sources of smoke, including liquid foodflavoring smoke, on seed germination was investigated (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%